Effects of low phosphorus supply on the availability of calcium and phosphorus, and musculoskeletal development of growing dogs of two different breeds. Issue 3 (2nd February 2018) - Kiefer‐Hecker, B.; Kienzle, E.; Dobenecker, B.
Summary: To investigate the impact of a selective reduction in dietary phosphorus (P) supply on healthy growing dogs, a total of 23 Beagles and 30 Foxhound crossbreds (FBI) were used in a feeding trial between 6 and 24 weeks of age. Sixteen Beagles and 19 FBI were fed with selectively reduced P concentrations (low phosphorus, LP). The remaining puppies received a completely balanced control diet (CON). With these diets, the P supply in the Beagles at the age of 12 weeks added up to 2.5 ± 0.6 (LP) and 9.8 ± 1.4 g P/kg DM (CON), and in the FBI 4.3 ± 0.9 (LP) and 13.0 ± 1.6 g P/kg DM (CON). Therefore, the LP Beagles received an average of 33 ± 11% of the recommended daily allowances (RDA) of P, the LP FBI 41 ± 11%. The calcium (Ca) concentration stayed unaltered and led to a Ca/P ratio above the recommended range of 1.3/1 to 2/1. The apparent digestibility (aD) of phosphorus was reduced in the LP Beagle; otherwise, the aD of both minerals was not affected by the P concentration of the diet. The renal excretion of P was reduced to zero in both LP groups while the renal calcium excretion increased significantly. Several of the puppies from both breeds showed impaired appetite, growth, skin and fur quality, and a few also clinically showed relevant signs of a disturbed musculoskeletal system after the LP feeding. A rapid loss of muscle strength and posture within hours led to severe deviation of the limb axis with hyperflexion of the joints but no radiological aberrations or signs of pain. Immediate transition of affected puppies to a balanced diet with sufficient phosphorus resulted in a complete recovery of the puppies in less than one month. The results demonstrate the importance of an adequate P supply on the healthy development of growing dogs.